HDAC2‐dependent miRNA signature in acute myeloid leukemia. Issue 18 (19th July 2019) - Conte, Mariarosaria; Dell'Aversana, Carmela; Sgueglia, Giulia; Carissimo, Annamaria; Altucci, Lucia
Abstract : Acute myeloid leukemia (AML) arises from a complex sequence of biological and finely orchestrated events that are still poorly understood. Increasingly, epigenetic studies are providing exciting findings that may be exploited in promising and personalized cutting‐edge therapies. A more appropriate and broader screening of possible players in cancer could identify a master molecular mechanism in AML. Here, we build on our previously published study by evaluating a histone deacetylase ( HDAC ) 2 ‐mediated miRNA regulatory network in U937 leukemic cells. Following a comparative miRNA profiling analysis in genetically and enzymatically HDAC2‐downregulated AML cells, we identified miR‐96‐5p and miR‐92a‐3p as potential regulators in AML etiopathology by targeting defined genes. Our findings support the potentially beneficial role of alternative physiopathological interventions. Abstract :